Impact of and recovery from seabed trawling in soft-bottom benthic communities under natural disturbance of summer hypoxia: A case study in subtropical Hong Kong - Xu, Wenzhe; Fleddum, Anne Lise; Shin, Paul K. S.; Sun, Jun (Frontiers in Marine Science, 2022)
Bottom trawling has widespread impact on the structure and composition of benthic communities. In this study, soft-bottom macrofauna in a heavily trawled area and an adjacent marine park that has been closed to bottom trawling for more than ten years were sampled, allowing to investigate the impact of and recovery from trawling. Both areas were equally affected by seasonal summer hypoxia. Polychaetes were the most abundant at trawled (78-86%) and non-trawled (85-94%) sites in both summer and winter. The non-trawled sites inside the marine park area had a lower level of species composition and abundance as compared to the trawled sites in summer, whereas in winter the benthic communities at these trawled and non-trawled sites appeared much similar with the majority of the identified taxa being dominated by new recruiting juveniles in both sampling areas. Results of permutational multivariate analysis of variance (PERMANOVA) on transformed infaunal abundance and biomass data revealed significant differences (p<0.05) between trawled and non-trawled treatments and seasons, as well as their interactions. Pair-wise a posteriori PERMANOVA further indicated significant differences for the abundance and biomass data in summer but insignificant differences in winter. PERMANOVA of the biological traits of infauna weighted with transformed biomass also confirmed significant difference for seasons only. Such findings imply that the effect of season was more important than that of trawling especially on the biological trait structure of the benthic communities. In addition, bottom trawling may contribute to a higher level of dissolved oxygen when the area suffered from hypoxia, resulting a higher biodiversity in the trawled area in summer. By comparing data taken prior to closure of the marine park from trawling, the recovery of infaunal community has been slow over the 12 years as a trawl-free area. Apart from natural disturbance of summer hypoxia, such recovery could also be complicated with the presence of artificial reefs deployed within the marine park, which may affect the hydrodynamics of the benthic environment and modify the community structure and function.